209k views
0 votes
What is the intermediate step in the form (x + a)2 = b as a result of completing the

square for the following equation?
x^2-7x = -9x – 2

User Snixtor
by
5.3k points

1 Answer

1 vote

Step-by-step explanation

Since we have the expression:

(x + a)^2 = b

And the quadratic expression:


x^2-7x\text{ = -9x - 2}

Adding +2 to both sides:


x^2-7x\text{ +2 = -9x}

Adding +9x to both sides:


x^2+2x+2=0

Now, rewriting the expression:


x^2+2x=-2

Now, completing the square of:


x^2+bx=c

We need to add b^2/4 to both sides:


(2^2)/(4)=(4)/(4)=1

Now, we get:


x^2+2x+1=-2+1

and get:


(x+1)^2=-1

Therefore, we need to take square roots of the expression to get:


√((x+1)^2)=√(-1)
x+1=i

Isolating x:


x=-1\pm i

Therefore:


x^2+2x+2=
=(-1+i)(-1-i)

User Makro
by
5.8k points